2000
DOI: 10.1007/s005350050351
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor of the liver with primary sclerosing cholangitis

Abstract: Inflammatory pseudotumor (IPT) of the liver is a rare benign variant of hepatic masses, and its exact etiology has not been elucidated. We report a case of IPT associated with primary sclerosing cholangitis (PSC). The patient was a 50-year-old man admitted to our hospital because of jaundice. Abdominal ultrasonography (US) and computed tomography showed multiple dilations of the intrahepatic bile ducts and multiple masses in the liver. On magnetic resonance imaging, the masses were slightly hypointense on T1-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
1
31
1
1
Order By: Relevance
“…The inflammatory pseudotumor (IPT) of the liver is a rare, benign tumor-like lesion [6,15], and about 60 cases have been reported in the English-language literature [17]. Some cases of IPT of the liver have been associated with malignant tumors [1, 7-9, 11, 13, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory pseudotumor (IPT) of the liver is a rare, benign tumor-like lesion [6,15], and about 60 cases have been reported in the English-language literature [17]. Some cases of IPT of the liver have been associated with malignant tumors [1, 7-9, 11, 13, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Many mechanisms and hypothesized etiologic factors like infections, trauma, autoimmunity reactions, radiotherapy, and local reaction to changes in the walls of bile ducts are suggested [1][2][3][4][5][6][7]10,13,[18][19][20][21][22][23][24][25][26]. Some microorganisms that access the portal vein including Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Gram-positive cocci and Actinomyces were regarded as causative agents.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections (Epstein-Barr virus [20], hepatitis B and C virus) [10,27] and parasitic infestations (Schistosoma mansoni) may play role in the pathogenesis [18]. Some authors suggested that disturbance of biliary drainage, e.g., due to biliary stones [1,7], recurrent pyogenic cholangitis [4,26] or sclerosing cholangitis is also important [25]. The tumor was also noted in HIV infected persons [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nonomuraet al reported a case of IPT with marked destructive and sclerosing cholangitis mimicking PSC (12). More recently, Toda et al reported a case of IPT with definite PSC (13). Autoimmunemechanism was suggested in the pathogenesis of PSC because of the presence of autoantibodies.…”
Section: Discussionmentioning
confidence: 99%